18-6m=5-4m

Simple and best practice solution for 18-6m=5-4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18-6m=5-4m equation:


Simplifying
18 + -6m = 5 + -4m

Solving
18 + -6m = 5 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
18 + -6m + 4m = 5 + -4m + 4m

Combine like terms: -6m + 4m = -2m
18 + -2m = 5 + -4m + 4m

Combine like terms: -4m + 4m = 0
18 + -2m = 5 + 0
18 + -2m = 5

Add '-18' to each side of the equation.
18 + -18 + -2m = 5 + -18

Combine like terms: 18 + -18 = 0
0 + -2m = 5 + -18
-2m = 5 + -18

Combine like terms: 5 + -18 = -13
-2m = -13

Divide each side by '-2'.
m = 6.5

Simplifying
m = 6.5

See similar equations:

| 3a+5b-7b= | | n+n+1+n+2=27 | | 2(w-4)=8w+10 | | 6/7=x/10.5 | | 27x-3=51 | | 2a+8=3a-1 | | 51x-3=27 | | 5(x-2)=5x-11 | | 2(x+10)+3x=85 | | 51x-27=3 | | 32-5x=50-3x | | 5x+2(17-4x)=4 | | 3.2-0.5x=5-0.3x | | 4b+25+3b=-50 | | -11p+20p-6p-8p-p=16 | | -6(2x-1)=25 | | 3/4n-8=-17 | | 11/20-5/20= | | (4b+6)(6-4)= | | -15t+14t=7 | | x+x+1+x+2+x+3=-22 | | 3(2-2x)=2(4+5x) | | 0.8(x-4)=2(0.4x+1.6) | | 59=8y-9 | | 9x-2(4x+10)+2=21 | | 14g-10g-g=9 | | -13=5x+12 | | 80+x+(3x-22)=180 | | 0.5x+3x+0.6=180 | | 6r+7-9r-19= | | 3/4g=−12 | | -9-4=5x+12 |

Equations solver categories